First report on the occurrence of aberrant extra dorsal fins in ompok bimaculatus (Bloch, 1794) from Godavari River Basin, India - Kantharajan, Ganesan; Chandran, Rejani; Singh, Rajeev K.; Tyagi, Lalit Kumar; Rana, Jai C.; Sarkar, Uttam Kumar (Springer, 2024)
This paper reports the occurrence of aberrant extra dorsal fins in a ‘Near Threatened’ butter catfish, Ompok bimaculatus (Bloch, 1794) for the first time from a reservoir ecosystem in Godavari River Basin. The specimen was taxonomically confirmed through morphological features and molecular attributes. This study also highlights the possible causes of such deformity in the natural fish populations of man-made ecosystems i.e., reservoirs.